2021
DOI: 10.1111/jar.12874
|View full text |Cite
|
Sign up to set email alerts
|

Static postural balance between male athletes with intellectual disabilities and their sedentary peers: A comparative study

Abstract: Intellectual disability is a complex dysfunction difficult to define accurately. According to Schalock et al. (2010), it is characterized by meaningful limitations in intellectual functioning and adaptive behaviour, expressed in conceptual, social and practical adaptive skills (Schalock et al., 2010). Many individuals with intellectual disabilities experience motor impairments. In this context, it has been demonstrated that people with intellectual disabilities have gait problems (Oppewal et al., 2018). Specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 65 publications
(77 reference statements)
0
13
0
1
Order By: Relevance
“…We did a power calculation that focused on the between-subjects factor of sport practice. A posturographic study between athletes and non-athletes with intellectual disability (Jouira et al, 2021) and another study comparing the balance of athletes and non-athletes without disabilities (Krampe et al, 2014) reported effect sizes f = 0.51 and 0.21, respectively. Thus, we expected the effect size for our study to be somewhere between those values.…”
Section: Participantsmentioning
confidence: 99%
“…We did a power calculation that focused on the between-subjects factor of sport practice. A posturographic study between athletes and non-athletes with intellectual disability (Jouira et al, 2021) and another study comparing the balance of athletes and non-athletes without disabilities (Krampe et al, 2014) reported effect sizes f = 0.51 and 0.21, respectively. Thus, we expected the effect size for our study to be somewhere between those values.…”
Section: Participantsmentioning
confidence: 99%
“…In a review of this literature, we located several studies comparing the dynamic and static balance differences between active and sedentary participants in several different sports (Bressel et al, 2007;Davlin, 2004;Kesilmis, 2017;Khuman et al, 2014). Moreover, a recent study comparing static balance between sprint runners with ID and their sedentary peers (Jouira et al, 2021) also found that runners had greater static balance than their sedentary peers. Nevertheless, to the best of our knowledge this is the first study comparing dynamic balance between athletes with ID and their sedentary peers.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, dynamic balance is important for running speed performance. To our best knowledge, only Jouira et al (2021) compared static postural balance between runners (sprint) with ID and their sedentary peers, and these authors found that sprint runners with ID had greater static balance than their sedentary peers. In the present study, we sought to evaluate dynamic postural balance in runners with ID and their sedentary peers because dynamic balance may also relate to daily life activities.…”
Section: Introductionmentioning
confidence: 99%
“…Amplification was included in each sensor with a 16-bit AN converter. The equipment required was a computer with a 32-bit operating system (Jouira et al, 2021).…”
Section: Methodsmentioning
confidence: 99%